Literasi Media Tangkal Hoax: Pendampingan Dan Penyuluhan Pada Siswa MA Miftahul Huda Pecalukan Untuk Menangkal Informasi Hoax Dalam Bermedia Sosial - Abdul Majid; Sri Yaumi; Muhammad Imron Rosadi (LPPM Universitas Yudharta Pasuruan, 2021)
The spread of hoaxes is part of the impact of the very rapid development of information over the last few years. The development of information technology has led to the emergence of a new public space, namely social media. Social media can have both positive and negative impacts. The negative impact, the spread of hoaxes has become uncontrollable so that it has the potential to trigger disruption of social order. Media literacy is education that teaches media audiences to have the ability to analyze media messages, to be responsible and to respond correctly when getting information. The target audience in this community service is MA Miftahul Huda Pecalukan student. Because MA students are students who are very vulnerable to the influence of Hoaxes that have the potential to trigger disturbances in society. This service is carried out to provide understanding to MA Miftahul Huda students about media literacy and they can also become agents of the media literacy movement in order to ward off hoaxes. The method used in community service is through seminars, discussions and workshops. With this method, it is hoped that two-way communication will occur, both between the resource person and the participants and among the participants themselves